(untitled) (World Economics and Finance Bulletin, 2023)
The rapid development in information and communication technology has considerably affected all scientific, service, health, media fields as well as government institutions services. The field of education comes at the forefront of the areas that have greatly been impacted in a positive way, as scientific resources and electronic books have become accessible to learners and researchers thanks to their availability on the websites of governmental and non-governmental scientific institutions. Moreover, researchers have also received a bonus of being granted a scientific status and material and moral rewards when they publish research and scientific articles. This has paved the way for learners to reach their goals. The outbreak of the Coronavirus has been an incentive for educational institutions to adopt e-learning in the world in general and in Iraq in particular, in the sense that pandemic has geared the attention of researchers and decision-makers of educational institutions towards e-learning and making it part of the learning methods for learners. E-learning can be defined as one of the methods of education, which depends on the presentation of educational content and the delivery of skills and concepts to the recipients through communication and information technology. It is one of the most important types of education at present. Information and communication technology is the language of modernity as e-learning technology has become one of the basic necessities for the development of educational systems. It is necessary to educate teaching staff, undergraduate and postgraduate students about the importance and role of e-learning and how to benefit from it. It is also important to stress the need to overcome obstacles and difficulties facing teaching staff and students when using e-learning and providing the necessary supplies for them.